Extraction of physical Schottky parameters using the Lambert function in Ni/AlGaN/GaN HEMT devices with defined conduction phenomena *Project supported by the French Department of Defense (DGA). (January 2017) - Latry, O.; Divay, A.; Fadil, D.; Dherbécourt, P.
Abstract: Electrical characterization analyses are proposed in this work using the Lambert function on Schottky junctions in GaN wide band gap semiconductor devices for extraction of physical parameters. The Lambert function is used to give an explicit expression of the current in the Schottky junction. This function is applied with defined conduction phenomena, whereas other work presented arbitrary (or undefined) conduction mechanisms in such parameters' extractions. Based upon AlGaN/GaN HEMT structures, extractions of parameters are undergone in order to provide physical characteristics. This work highlights a new expression of current with defined conduction phenomena in order to quantify the physical properties of Schottky contacts in AlGaN/GaN HEMT transistors.